A bi-directional Mendelian randomization study of sarcopenia-related traits and type 2 diabetes mellitus - Chen, Simin; Yan, Shikang; Aiheti, Nuerbiyamu; Kuribanjiang, Kaidiriyan; Yao, Xuemei; Wang, Qian; Zhou, Tao; Yang, Lei (Frontiers in Endocrinology, 2023)
Background Previous studies have reported an association between sarcopenia and type 2 diabetes mellitus (T2DM), but causation was prone to confounding factors. A more robust research approach is urgently required to investigate the causal relationship between sarcopenia and T2DM. Methods The bi-directional two-sample MR study was carried out in two stages: Sarcopenia-related traits were investigated as exposure while T2DM was investigated as outcome in the first step, whereas the second step was reversed. The GWAS summary data for hand-grip strength (n = 256,523), appendicular lean mass (ALM, n = 450,243), and walking pace (n = 459,915) were obtained from the UK Biobank. T2DM data were obtained from one of the biggest case-control studies on diabetes (DIAGRAM; n = 180,834 cases and 492,191 controls), which was published in 2022. The inverse-variance weighted (IVW) approach was used to obtain MR estimates, and various sensitivity analysis was also performed. Results Genetically determined low hand-grip strength was associated with an increased incidence of T2DM (OR = 1.109; 95% CI, 1.008–1.222; p = 0.0350). T2DM risk was reduced by increasing ALM and walking pace: A 1 kg/m2 increase in genetically determined ALM decreased the risk of T2DM by 10.2% (OR = 0.898; 95% CI, 0.830–0.952; p < 0.001). A 1 m/s increase in genetically determined walking pace decreased the risk of T2DM by 90.0% (OR = 0.100; 95% CI, 0.053–0.186 p < 0.001). The relationship was bidirectional, with T2DM as a causative factor of sarcopenia-related traits (p < 0.05) except for ALM (β = 0.018; 95% CI, −0.008 to −0.044; p = 0.168). Conclusions Hand-grip strength and T2DM had a bidirectional causal relationship, as did walking pace and T2DM. We suggest that sarcopenia and T2DM may mutually have a significant causal effect on each other.